Soybean response to fertilization and potassium availability in an Oxisol (Haplorthox) - Borkert, Clóvis Manuel; Farias, José Renato Bouças; Sfredo, Gedi Jorge; Tutida, Fábio; Spoladori, Claudio Luis (Pesquisa Agropecuaria Brasileira, 1997)
With the objective of studying the best technique for corrective K fertilization and the residual effect of K fertilization, a long term experiment was run in an Oxisol (Haplorthox), in Mauá da Serra, PR, Brazil. In the first five growing seasons (1983 to 1987), rates of potassium chloride of 0, 40, 80, 120 and 200 kg of K2O/ha were applied every year in the seed furrow and by broadcasting. In the next five growing seasons, soybean was cultivated without K fertilization. Treatment effects were evaluated on exchangeable-K in the soil, and K content in the leaves of the upper third of the plant and in the seeds, and on soybean yield. It was concluded that soybean can not achieve high yields when cultivated in an Oxisol (Latossolo Roxo distrófico - LRd) low in exchangeable K (0,10 cmolc dm-3) without K soil correction with 150 to 200 kg of K2O/ha plus a yearly maintenance application of 80 kg of K2O/ha. Soybean leaves of the upper third with less than 12.5 g kg-1 of K content show K deficiency symptoms. High yields are always associated with K content in leaves higher than 17.1 g kg-1.